Order of Mind and Society: Reading The Winter’s Tale vis-à-vis Selected Teachings of Buddha - Rijal, Shiva (Journal of Innovation in Academia, 2022)
This paper reads The Winter’s Tale by William Shakespeare and Buddha’s teaching on mindfulness collected mainly in The Middle Length Discourse of Buddha and The Dhammapada together. Unable is the human mind to predict the kind of thoughts it might experience next, same is the case with life that human beings live in this universe. Leontes in the play finds it hard not to believe on his thoughts. Since he fails to watch his own thoughts, he loses several precious belongings in his life. Buddha in his teachings makes us cautious about the trick our own thoughts can play upon the beholders. Be aware of own thoughts is the call. Two different forms of expression produced over two different times and places, the play and the teachings as tales of human mind may help readers to articulate one with the help of other. The paper concludes that together these texts reveal to the readers that society is run as much as by people in power politically and militarily as it is by the people who are mindful and act responsibility. Without mindful individuals, powerful rulers alone fail to provide order to their society and life.